HARMFUL SOCIO-CULTURAL PRACTICES AFFECTING THE GIRL-CHILD AMONG THE KAMBARI OF NIGER STATE, NIGERIA (2015)
Socio-cultural practices which have severe consequences on the overall well-being of the girl-child have drawn attention worldwide. Despite extensive empirical evidence, there is a dearth of studies in Nigeria on the situation of the girl-child among the Kambari of Niger State. This study, therefore, examined the harmful socio-cultural practices affecting the Kambari girl-child. Max Weber’s social action, patriarchy, and sex role theories provided the theoretical framework. A triangulation approach was adopted in data collection. A household survey was conducted among 1598 respondents. Each was a pair of adult males (385) and their sons (385) as well as adult females (414) and their daughters (414). A four-stage sampling technique was used to select respondents from 63 Enumeration Areas in the six Kambari-dominated Local Government Areas (LGAs) of Niger State: Agwara, Borgu, Magama, Mariga, Mashegu and Rijau LGAs. Two sets of structured questionnaires were used to collect information on socio-demographic characteristics, cultural construction of girlhood, familial roles and household practices from adults, boy and girl-children. Fifteen Focus Group Discussions on gender socialisation, gender relations, household practices, and socio-cultural factors were conducted with male and female adults, boy and girl-children in the LGAs. Fourteen In-depth Interviews were conducted with religious clerics, traditional rulers, male and female community leaders. Twelve case studies of girl-children were also conducted. Quantitative data were analysed using descriptive statistics and logistic regression at p≤0.05. The qualitative data were content analysed. Adult respondents’ age was 40.3±10.0 years, 98.1% were married, and 81.7% were farmers. The mean age for girl-children was 13 years. Most of the respondents were rural dwellers (82.0%). Most of the respondents (97.1%) opined that the status of the girl-child was very low relative to the boy-child. About 99% affirmed that girl-children were disadvantaged with regard to opportunities and privileges. The girl-child faced household discriminatory practices in domestic work assignment (79.0%), education (78.4%) and restrictive food taboos (32.2%). Traditional leaders and significant others approved such practices. About 67% of girl-children perceived these practices as acceptable to the Kambari. Adult respondents’ gender (Odds Ratio (OR):5.426), education (OR: 4.156), religious affiliation (OR: 3.888), place of residence (OR: 1.723), ideational variables such as pattern of decision-making (OR: 5.707), childhood experiences (OR: 4.396), non-valuation of women’s role in decision-making (OR: 1.535), and conception of gender roles (OR: 1.317) were significant predictors of the likelihood of exhibiting discriminatory practices against the girl-child. Conception of gender roles, gender socialisations, son preferences, cultural construction of girlhood, and valuation of the girl-child, decision-making, gender stereotyping engender discriminatory practices against girl-children. Child betrothal, early marriage, burden of domestic work, child labour, preference for boy-education disempowered girls, while food taboos deprived them of nutritional well-being and good quality of life. These harmful socio-cultural practices which tend to be discriminatory in nature against the girl-child were deeply rooted in Kambari tradition and have persisted. Serious attention should be given to community mobilisation and sensitisation to address harmful socio-cultural practices which tend to disempower the girl-child among the Kambari.